Analisis Dampak Penggunaan Teknologi dan Peningkatan Pengetahuan pada Pendapatan Petani Kopi di Kecamatan Sangir Kabupaten Solok Selatan - Redho Oktaviandi; Baginda Persaulian (Universitas 17 Agustus 1945 Semarang, 2025)
This research was motivated by the uneven use of technology in coffee plantations, resulting in unstable harvests and poor quality. This is also caused by a lack of knowledge in processing coffee in Sangir District, South Solok Regency, so that the income obtained by farmers is less than optimal. So the researcher wants to analyze the impact of the use of technology and increased knowledge on the income of coffee farmers in Sangir District, South Solok Regency. The method in the study is Qualitative Research. Collecting data through interviews and in-depth observations with local coffee farmers. The study also uses secondary data from various sources such as data from the Central Statistics Agency (BPS), data analysis is carried out by means of data reduction, data presentation and drawing conclusions. The results of this study indicate that the use of modern technology and increased knowledge have a very significant impact on the income of coffee farmers in Sangir District, South Solok Regency. The combination of the use of technology and increased knowledge is one solution to improve the welfare of coffee farmers, with the right support coffee farmers can increase their productivity, get better prices and ultimately improve their standard of living.